Sensational pedagogies: Learning to be affected by country. Issue 5 (20th October 2017) - Harrison, Neil; Bodkin, Frances; Bodkin-Andrews, Gawaian; Mackinlay, Elizabeth
ABSTRACT: Student capacities to actively listen, sense and feel are often relegated to lower order skills in an education system increasingly governed by measurable outcomes. While most school-based pedagogies focus their approach on cognition, this paper considers how we might make sense of the affective experiences that often resist the deep thinking, independent learning and explanation so often required of students. The guiding aim is to explore how affective learning can be better understood through an Indigenous Australian concept of Country . We apply the pedagogical work of Elizabeth Ellsworth, along with Lacanian psychoanalytic theory to explore ways in which sensation and affect are already a method of learning, but ones that are substantially under-valued in designed curricula. A series of interviews with senior Aboriginal people are presented to assist in understanding the various ways in which affect can lead to thought. The authors present three case studies to highlight how knowledge can be taught through affective experiences of Country.